REVOLUTIONIZING TENNIS EXCELLENCE: THE SWISS BALL SAGA AND ITS GAME-CHANGING IMPACT ON PLAYERS' PHYSICAL PROWESS - Dr. R. SEVI; WASEEM AHMAD BHAT (RADJA PUBLIKA, 2024)
ABSTRACT The objective of this investigation is to scrutinize the impact of Swiss-ball training on chosen physical factors among male tennis players. Methodology: This study adopts an experimental research approach with a pre- and post-test design, incorporating both a swiss ball training group and a control group. Thirty male participants were chosen for this research and divided into two groups: Group A (n=15) designated as the experimental group and Group B (n=15) as the control group. Participants' ages encompassed a range from 18 to 23 years. The SBT program was structured to include three sessions every week, and each session extended for duration of 45 minutes. Subjects were assessed both before and after the 8-week session. In the realm of statistical scrutiny, ANCOVA and the prowess of SPSS 22 were harnessed for meticulous analysis. The confidence threshold for the level of impact was set at 0.05.. Observations and Discussion: The results pointed to a significant influence of SBT on the designated physical traits, encompassing muscular endurance, and flexibility. Conclusion: It is manifestly clear that engaging in SBT proves to be advantageous for the enhancement of physical variables. Expanding the number of training sessions per week is poised to yield more substantial effects, contributing to a noteworthy improvement in the overall fitness levels among the student population. Keywords: Physical, Exercise, Muscular Endurance, Flexibility and Swiss Ball training (SBT).